Determining factor affecting employee performance in telecommunication sector a case of Telekom Malaysia - Ahmad Salehin, Nursyadia Izati (2020)
The trend of competition among firms is on the rise as well as the need for these firms to effectively respond to the changes in operational conditions and employees’ personal requirement. This scenario has made it a necessity for firms to identify the factor affecting employee performance. This study integrates the body of literature on employee performance and develops a conceptual framework that depicts plausible impacts of employee participation, employee relations and job involvement on employee performance. Herzberg two-factor theory is taken into account for this study as a theoretical anchor. The study uses a sample of human resources employees from two departments working in Telekom Malaysia Berhad. The data from 74.62% out of 130 human resources employees are collected then analyzed by using IBM SPSS Statistics (Version 25.0). The result from Multiple Regression analysis indicated that only two dimensions in employee performance, which are employee participation and job involvement have significant and positive relationships with employee performance while employee relations is not substantial. Thus, from the analysis, a predictor of employee participation represented as the most significant variable affecting employee performance of employee at Telekom Malaysia'